Exploring the impact of play-based learning on teacher satisfaction, stress, and learners’ collaboration - Sulaimon, Jamiu; Adebayo, Abdullateef Adeshina; Manditereza, Blandina (Institut Agama Islam Negeri Langsa, 2025)
This study investigated the effects of play-based learning on teacher satisfaction, stress levels, and collaborative learning among primary education learners. Employing a descriptive survey design, the study sampled 200 early childhood education practitioners in Ilorin South Local Government Area, Kwara State, Nigeria, selected through simple random sampling. Data were collected using a validated instrument—the